2015
DOI: 10.1186/s11671-015-0866-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based optical modulators

Abstract: Optical modulators (OMs) are a key device in modern optical systems. Due to its unique optical properties, graphene has been recently utilized in the fabrication of optical modulators, which promise high performance such as broadband response, high modulation speed, and high modulation depth. In this paper, the latest experimental and theoretical demonstrations of graphene optical modulators (GOMs) with different structures and functions are reviewed. Particularly, the principles of electro-optical and all-opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 84 publications
(116 reference statements)
0
45
0
Order By: Relevance
“…Consisting of only one or a few atomic layers, 2D materials exhibit exotic electronic and optical properties that are distinctively different from their bulk parental materials, opening new opportunities for nanoscale electronics and photonics . Among various possibilities, optical modulation that controls the intensity, phase, or polarization of a light beam passing through these ultrathin materials has been attracting increasing attentions in recent years …”
Section: Introductionmentioning
confidence: 99%
“…Consisting of only one or a few atomic layers, 2D materials exhibit exotic electronic and optical properties that are distinctively different from their bulk parental materials, opening new opportunities for nanoscale electronics and photonics . Among various possibilities, optical modulation that controls the intensity, phase, or polarization of a light beam passing through these ultrathin materials has been attracting increasing attentions in recent years …”
Section: Introductionmentioning
confidence: 99%
“…Later on, several devices operating at visible spectral range have been demonstrated [24][25][26]. Other preferable photoconductor substrates are semiconductors as a-Si:H, crystalline silicon, gallium arsenide, indium phosphate and cadmium tellurite [27,28]. Usually, transparent indium tin oxide (ITO) conductive layers are preliminary deposited on the outer side of the photoconductive plate and the inner side of glass substrate and coated with polyvinyl alcohol (PVA) for planar alignment of the LC molecules.…”
Section: Organic-inorganic Structure Design and Principle Of Operationmentioning
confidence: 99%
“…Blake et al [9] rst demonstrated a liquid crystal device with graphene electrode, where a small graphene sheet was used as a contact at one side of the LC cell, supported with ITO layer from another side. Afterward, several attempts have been reported for complete replacement of ITO with graphene in LC displays [10]. For example, LC cell using graphene conductive layers have been reported as competitive to LC cell using ITO contacts, however su ering with the graphene mechanical instability during the LC rubbing alignment procedure [11].…”
Section: Introductionmentioning
confidence: 99%